Microstructure and Geochemical Investigations of Chalcedony - TEKBAS CANDAR, M. (Asian Journal of Chemistry, 2009)
Chalcedony from Turkey has been investigated by scanning-electronmicroscopy and petrographic microscopy. The geochemical analyseswere also carrried out. Chalcedony is a microcrystalline variety of silicaSiO2. Wall-lining chalcedony is parallel fibrous consisting of smallercrystallites. Chalcedony is regarded as a secondary, metastable, transitionalphase.